Treatment of Chronic Hepatitis B With Tenofovir At The University Teaching Hospital Campus of Lome (Togo) - Aklesso Bagny; Oumboma Bouglouga; Late Mawuli Lawson-Ananissoh; Djatougbe AE Akolly; Abago Balaka; Mohaman awalou Djibril; Yao D Atakouma; Datouda Redah (Journal of Spleen And Liver Research, 2017)
Aims: To describe the clinical, biological and evolutionary features of mono infected patients treated with tenofovir in Togo. Method: It is a descriptive, prospective study. Patients were treated with Tenofovir Disoproxil Fumarate (TDF). The inclusion criteria were: active chronic HBV (HBs Ag-positive for more than 6 months, high aminotransferases, the HBV –DNA ≥ 2000 IU / ml for HBeAg negative or ≥ 20 000 IU / ml for HBeAg positive and significant fibrosis) and absence of HCV, HDV, or co-infection HIV. Results: Among patients with HBV in our department, only 10.68% were treated with TDF. The mean age of patients was 33.01±9.81years. There was male predominance (68%). The circumstances of discovery were mainly during blood donation (65.3%) and a routine checkup (14.7%). Clinical examination was normal in most of cases (86.7%) apart from hepatomegaly (9.3%) and icterus (4%).) The HBeAg was negative in 89.3%; the average DNA was 7.56 ±8.01 log10 IU/ml. Abdominal ultrasonography was performed in all patients and we found hepatomegaly (18.67%), splenomegaly (10.67%), and ascites (5.3%). The assessment of fibrosis and activity had enabled to find a fibrosis higher or equal to 2 in 12 cases (48%) and an activity higher or equal to 2 in 9 cases (36%). The clinical and virologic outcome was marked by an undetectable viral load (HBV-DNA˂10 IU/l) in 89.3% of the patients after 1 year of treatment. Conclusion: TDF had helped to find out an undetectable viral load in in 89.3% of the patients after one year of treatment.
Keywords: Hepatitis B